(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
This research aims to evaluate the Mastery Learning Model in improving students’ reading skills. The study was conducted at MTs Al-Hikmah Marihat Bandar and involved 56 seventh-grade students, divided into two groups: the experimental group and the control group, with 28 students in each. The research employed a true experimental quantitative method using a pre-test and post-test design. The experimental group was taught using the Mastery Learning model, while the control group received conventional instruction. Data were analyzed using SPSS 26.0, including tests of normality, homogeneity, ANOVA, and paired sample t-test. The findings showed that the post-test mean score of the experimental group (87.29) was significantly higher than that of the control group (74.86). The results of ANOVA and t-test indicated a significant difference between the two groups, with Fₕ = 40.142 > Fₜ = 4.02 and tₕ = 6.061 > tₜ = 1.703. Based on these results, the null hypothesis (H₀) is rejected and the hypothesis (Hₐ) is accepted. This confirms that the Mastery Learning model can improve students’ reading skills